Development of Physics Learning Video Media Based on Microlearning - Nur Akhyar Basri; Khaeruddin Khaeruddin; Usman Usman (Universitas Lambung Mangkurat, 2023)
This study aims to produce learning media through microlearning-based physics learning videos. The feasibility test is measured through validation by experts and responses from teachers and students. So, the problem formulation for this research is: (1) How is the feasibility of the developed microlearning-based physics learning videos? (2) How did the Class XI MA PP DDI As-Salman Allakuang students respond to the developed microlearning-based physics learning video? (3) What is the teacher's response to the microlearning-based physics learning video? This research uses research and development methods, often called research and development (R&D). In this study, the ADDIE development design was used. This design consists of five development stages: analysis, design, development, implementation, and evaluation. The media and material validation results by the two validators were analyzed using the Gregory model, and the results of Gregory's analysis obtained the coefficient. Gregory's internal consistency is ≥ 0.75. In this case, microlearning video media can be used. As for the results of the analysis of student responses to this development, the video media received a very good response from students, with 98 students in a score interval of 81–100 in the